Biological Degradation of Chlorpyrifos and Monocrotophos by Bacterial Isolates - KaviKarunya, S (International Journal of Pharmaceutical & Biological Archive, 2012)
Biological Degradation of Chlorpyrifos and Monocrotophos by Bacterial Isolates